PERCEIVED COMPUTER SKILLS IN LEARNING COMMUNICATION AND SATISFACTION IN ONLINE AMONG COLLEGE STUDENTS IN PANABO CITY: A CORRELATIONAL ANALYSIS - Krisha Claire H. Dionola ,; Arvine Jane B. Del Carmen,; Jhon Lurym D. Delos Santos,; Marianne N. Dojo,; Jean Michelle B. Catipay,; Mark Van M. Buladaco, (International Journal of Innovations in Engineering Research and Technology, 2022)
As time passes, everything evolves and significantly impacts our daily lives. Computer-related methods are one of them, and we develop abilities that we may apply in everyday situations, particularly in learning communication. Whenever it comes to this subject, technological skills are increasingly important. In this study, we assess and correlate the slope of computer skills and satisfaction online of our preferred respondents, the college students of Panabo City. Researchers employed non-experimental quantitative methods. The research question was approached using a correlational research strategy. We evaluate the factors' influence and relationship of the said variables. We'll use a questionnaire divided into two sections to examine our respondents: computer skills and satisfaction. Afterward, we assess the potential outcomes for the results presented in this study.